Fast Calibration Methods for Resistive Sensor Readout Based on Direct Interface Circuits - Hidalgo-López, José Antonio; Botín-Córdoba, Jesús Alberto; Sánchez-Durán, José Antonio; Oballe-Peinado, Óscar (MDPI, 2019)
A simple method to measure the resistance of a sensor and convert it into digital information in a programmable digital device is by using a direct interface circuit. This type of circuit deduces the value of the resistor based on the discharge time through it for a capacitor of a known value. Moreover, the discharge times of this capacitor should be measured through one or two resistors with known values in order to ensure that the estimate is not dependent on certain parameters that change with time, temperature, or aging. This can slow down the conversion speed, especially for high resistance values. To overcome this problem, we propose a modified process in which part of the discharge, which was previously performed through the resistive sensor only, is only conducted with the smallest calibration resistor. Two variants of this operation method, which differ in the reduction of the total time necessary for evaluation and in the uncertainty of the measurements, are presented. Experiments carried out with a field programmable gate array (FPGA); using these methodologies achieved reductions in the resistance conversion time of up to 55%. These reductions may imply an increase in the uncertainty of the measurements; however, the tests carried out show that with a suitable choice of parameters, the increases in uncertainty, and therefore errors, may be negligible compared to the direct interface circuits described in the literature.
Keywords: Detectores; Direct interface circuits; Calibration methods; Error analysis; Resistive sensor; Interface sensor; Time-based measurement